Work without stress building a resilient mindset for lasting success - Roger, Derek 1946-; Petrie, Nick (McGraw Hill Education on BrillianceAudio, 2016)
An evidence-based, practical program to prevent stress by developing resilience. Why do some people get stressed while others stay resilient? According to research, the process of rumination-thinking over and over about events and attaching negative emotions to them is what causes stress and not the events themselves. The antidote to rumination is resilience, the capacity to cope with challenges and thrive under adversity. A critical professional and leadership skill, resilience can be learned and developed. Based on 30 years of lab research and controlled-trial case studies, this essential guide presents a proven step-by-step program to enhance individual and organizational performance.